Prinsip Halalan Thayyiban dan Deteksi Tadlis Mutu pada Sistem Prasmanan di Bleusky Resto Semarang - Sahrial Ardiansyah; A. Muhyiddin Khotib; Diva Tiara Anindita; Sita Nurmasitah (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Culinary quality evaluation is often dominated by conventional marketing, whereas Muslim consumers require a religio-ethical approach based on Islamic law. This study aims to analyzes the food and beverage quality in the breakfast buffet system at Bleusky Resto Semarang through contemporary Sharia Economic Law. The research method used in this research is empirical legal research applied a sequential integrative approach. Primary data were gathered from a survey of 33 customers, while secondary data came from fiqh muamalah literature. Analysis combined percentage descriptive statistics and content analysis via deductive-inductive reasoning. The research results show that the restaurant's operations generally comply with sharia, reflected by customer satisfaction regarding halalan thayyiban and hybrid contract mechanisms on dishes' freshness (84.90%) and fruit options (91.00%). However, a critical gap potentially triggering tadlis quality issues (information asymmetry) was found in beverages, where using fresh fruits for juice scored the lowest (57.50%). Complaint management is vital for enforcing Khiyar al-Aib to protect Muslim consumers, ensuring mutual consent and the protection of life.